Assessment of quality of life for affected women singleton pregnancies in Iraq and the diagnosis of pregnancy complications (Texas Journal of Medical Science, 2023)
Uterine rupture occurs when the integrity of the uterine wall is lost. The most common risk factor is having had previous uterine surgery, such as a caesarean section. Uterine rupture is not very frequent, but it is a complication of pregnancy or childbirth that in more serious cases (complete or catastrophic uterine rupture) can cause death of both mother and fetus. Objective: This paper aims to study the assessment of quality of life for affected women singleton pregnancies in Iraq and the diagnosis of pregnancy complications. Patients and Methods: In this study, a descriptive cross-sectional study was applied to study assessment of quality of life for affected women singleton pregnancies in Iraq and the diagnosis of pregnancy complications from 4th July 2021 to 11th June 2022. Data were collected for 90 patients different hospitals in Iraq, where the patients were divided into two groups, the first group of patients, which included women singleton pregnancies patient which included (50), and the second group, control group, which include (40) patients. A statistical study was conducted for women singleton pregnancies patient using the SPSS program. Results and Discussion: Uterine rupture occurs when the uterus ruptures because of pressure during pregnancy, labor or delivery. The uterus can rupture in some or all of its layers, compromising the oxygen supply to the fetus and causing severe bleeding in the mother. Also, Uterine rupture occurs most frequently along the scar line in women who have had previous caesarean sections. Other predisposing factors include congenital uterine abnormalities, trauma and other surgical procedures, and other surgical procedures such as myomectomy or open maternal-fetal surgery where This study relied on the Apgar score distribution of women singleton pregnancies patient, where it was divided into two types of degree and Apgar 5 min < 5 and contained 15 with 30% for the group of women singleton pregnancies patient, but the control group included 27 with 67.5% while Apgar 1 min < 5 was 35 and 70% for the singleton pregnancies patient group and 13, which represented 32.5% with the total number of cases. Conclusion: The incidence of uterine rupture is increasing due to the increase in vaginal deliveries after previous cesarean sections. Our study concludes that the control group was more successful and superior to singleton pregnancies patient group, as a result of what the results of the study showed in evaluating the patients' quality of life as well as the complications affecting both groups.